Narrating Genocide: Time, Memory, and Blame. Issue 1 (19th October 2016) - Nyseth Brehm, Hollie; Fox, Nicole
Abstract : More than 20 years have passed since the Rwandan genocide, yet we know little about how Rwandans remember the violence. This article draws upon more than 100 interviews with genocide survivors to assess collective memories of the atrocity. We find that survivors organize their narratives by conceptualizing the genocide as a watershed event that divides time into two distinct eras. When discussing the pregenocide period, survivors focus on macrolevel events and structures, locating blame for the genocide in institutions rather than on Rwandan citizens. By contrast, narratives of life after the genocide focus on perceived progress since 1994. We interpret these findings in light of the state's memory projects, the potential functionality of the memories, and the time needed for collective memories to resonate.